PROVOKING CREATIVITY IN BUSINESS: THE IMPACT OF PROMOTION AND PREVENTION PROBLEM-FRAMING ON CREATIVITY IN THE COVID-19 ERA - Askania Faza, Imala (PEOPLE: International Journal of Social Sciences, 2024)
Amidst the pivotal role of creativity in business survival, particularly accentuated by the recent COVID-19 pandemic, this study puts importance on the managers’ influence on guiding employee creativity. Grounded in regulatory focus theory, prior research traditionally favored promotion-focus over prevention-focus in shaping creativity. However, this study challenges this notion by investigating the impact of promotion and prevention problem-framing on creativity and hypothesizing whether previous findings remain robust even in the unprecedented changes brought about by the pandemic. Conducting an online survey with 218 British students, randomly assigned to promotion or prevention conditions, participants generated creative ideas linked to health improvement or maintenance. Unexpectedly, prevention problem-framing exhibited a slightly greater influence on creativity than promotion problem-framing, offering quite a novel perspective. While participants generally reported a relaxed attitude towards the pandemic, awareness of its inherent risks persisted. These findings highlighted the dynamic interplay between problem-framing and creativity, especially in unprecedented situations, emphasizing the need for managerial flexibility in leveraging these dynamics to enhance employee creativity.